Investigation of the Head Impact Power of a Sepak Takraw Ball on Sepak Takraw Players - Iskandar, Hasanuddin; Zahari, Taha; Nukman, Y.; Norhafizan, Ahmad; Raja Ariffin, Raja Ghazilla; Tuan Mohammad Yusoff Shah, Tuan Ya (Kementerian Pendidikan Malaysia, 2015)
Sepak takraw is a traditional sport in Asia in which the players use various parts of their bodies to hit the ball, with the exception of their hands. Unlike other sports such as soccer, boxing, and rugby, it is observed that none of the studies in the literature have examined the injuries resulting from the impact of the sepak takraw ball on the players’ heads during a game. This study was initiated following the incidents of the 24th SEA Games in Korat, Thailand, in year 2007, whereby a number of players from the Malaysian Sepak Takraw Association (PSM) had to withdraw themselves from the championship. These players suffered from headaches which were believed to be caused by the impact of the sepak takraw ball, considering the fact that heading is one of the basic movements used to hit the ball. Moreover, it is expected that the sepak takraw ball travels at high velocities during the game. Hence, the objective of this study is to investigate the impact of the sepak takraw ball and its corresponding level of head injury among sepak takraw players in Malaysia by means of numerical simulations and experiments. In order to achieve this objective, a model of the scalp, skull, cerebrospinal fluid and brain is first developed and simulations are then carried out using finite element analysis (FEA) software. The results show that the maximum speed of the sepak takraw ball before heading is 13.581 m/s while the maximum impact force on the head obtained from the simulations is 688.11 N. The maximum displacement and maximum linear acceleration of the brain’s centre of gravity is found to be 0.0080 m and 1674.5 m/s2, respectively, while the head impact power (HIP) is determined to be 11.366 kW. According to Newman et al. (2000), the probability of concussion is 39% and based on the results obtained in this study, it can be concluded that the players may suffer from mild traumatic brain injuries (MTBI) due to the high impact of the sepak takraw ball during heading. Hence, it is recommended that the players wear protective headbands to reduce the impact during heading and prevent the occurrence of MTBI in the long term.